Techniques and Current Role of Sentinel Lymph Node (SLN) Concept in Gastric Cancer Surgery - Symeonidis, Dimitrios; Tepetes, Konstantinos (Frontiers in Surgery, 2019)
Gastric cancer patients represent a rather divergent patient group and in certain carefully selected cases of early forms of gastric cancer the D2 gastrectomy could be considered a more radical procedure than the biological and oncological characteristics of the primary tumor on the gastric wall would require. As any unnecessary dissection increases morbidity without always respective survival benefits, an approach that could accurately predict and actually dictate the exact extent of lymph node dissection would be ideal. It is more than logical the assumption that the standard D2 lymphadenectomy could represent an overtreatment in distinct patients groups such as patients with early gastric cancer with favorable pathological characteristics and clinically negative nodes not suitable for endoscopic treatment because this early stage disease shows limited lymph node metastasis incidence and excellent overall survival. Considering that the D2 gastrectomy has a negative impact on the quality of life of gastric cancer patients due to the post-gastrectomy functional results, a concept of a more targeted lymph node dissection, when appropriate, is certainly appealing. It is yet to be proven whether sentinel lymph node navigation surgery can fulfill such expectations providing the appropriate balance between morbidity and oncological safety in selected gastric cancer patients.